Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/ijms18061313
|View full text |Cite
|
Sign up to set email alerts
|

Soluble (Pro)renin Receptor and Obstructive Sleep Apnea Syndrome: Oxidative Stress in Brain?

Abstract: (Pro)renin receptor ((P)RR) is a multi-functional molecule that is related to both the renin-angiotensin system (RAS) and vacuolar H+-ATPase (v-ATPase), an ATP-dependent multi-subunit proton pump. Soluble (P)RR (s(P)RR), which consists of the extracellular domain of (P)RR, is present in blood and urine. Elevated plasma s(P)RR concentrations are reported in patients with chronic kidney disease and pregnant women with hypertension or diabetes mellitus. In addition, we have shown that plasma s(P)RR concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…These results are consistent with the observations that plasma sPRR concentrations are independent of plasma prorenin/renin and aldosterone levels (Nguyen G et al, 2014). OSAS is characterized by intermittent hypoxia, resulting in oxidative stress in the multiple organs, contributing to the elevation of plasma sPRR levels in patients with OSAS (Takahashi K et al, 2017). In support of this possibility, hypoxia has been reported to significantly increase intracellular sPRR levels in human placental trophoblast cells (Suda C et al, 2020).…”
Section: Sprr In Cancers: a Novel Diagnostic Biomarker?supporting
confidence: 89%
“…These results are consistent with the observations that plasma sPRR concentrations are independent of plasma prorenin/renin and aldosterone levels (Nguyen G et al, 2014). OSAS is characterized by intermittent hypoxia, resulting in oxidative stress in the multiple organs, contributing to the elevation of plasma sPRR levels in patients with OSAS (Takahashi K et al, 2017). In support of this possibility, hypoxia has been reported to significantly increase intracellular sPRR levels in human placental trophoblast cells (Suda C et al, 2020).…”
Section: Sprr In Cancers: a Novel Diagnostic Biomarker?supporting
confidence: 89%
“…OSAHS is an oxidative stress disease, which indicates the role of intermittent hypoxia-induced oxidative stress in the pathogenesis of OSAHS. 17,18) We found that intermittent hypoxia significantly increased the ROS levels in the hippocampus, significantly decreased Mn-SOD and CTA expression, and did not affect Cu/Zn-SOD expression levels. Mn-SOD is expressed in the mitochondria; therefore, oxidative stress may predominantly occur in the mitochondria.…”
Section: Discussionmentioning
confidence: 74%
“…Third, circulating sPRR was reduced by 80% and adipose PRR protein expression was suppressed by adipocyte-specific deletion of PPARγ (FKO), but supplementation of sPRR in null mice significantly improved glycemic control. A better understanding of the adipose origin of circulating sPRR is clinically relevant, because elevated plasma sPRR is associated with early pregnancy (11,12), preeclampsia (39,40), gestational diabetes mellitus (12,14), renal dysfunction in patients with heart failure (13), obstructive sleep apnea syndrome (15,41,42), and CKD due to hypertension and type 2 diabetes (43).…”
Section: Discussionmentioning
confidence: 99%